2014
DOI: 10.1103/physrevd.90.016001
|View full text |Cite
|
Sign up to set email alerts
|

Are there tetraquarks at largeNcin QCD(F)?

Abstract: Weinberg recently pointed out a flaw in the standard argument that large Nc QCD with colorfundamental quarks [QCD(F)] cannot yield narrow tetraquark states. In particular, he observed that the argument does not rule out narrow tetraquarks associated with the leading-order connected diagrams; such tetraquarks would have a width scaling as N −1 c . It is shown here, however, that while the standard analysis of tetraquarks does not rule them out, a more thorough analysis rules out quantum-number exotic tetraquark… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(113 citation statements)
references
References 32 publications
5
106
2
Order By: Relevance
“…In [36] it is shown that the Coleman-Witten lore that no tetraquarks occur at large N is not related to the fact that they did not consider all possible ways of cutting the diagrams. Therefore, tetraquarks can be made the way suggested in [31], but with the concerns discussed in [37].…”
Section: Jhep06(2016)160mentioning
confidence: 99%
“…In [36] it is shown that the Coleman-Witten lore that no tetraquarks occur at large N is not related to the fact that they did not consider all possible ways of cutting the diagrams. Therefore, tetraquarks can be made the way suggested in [31], but with the concerns discussed in [37].…”
Section: Jhep06(2016)160mentioning
confidence: 99%
“…Tetraquarks in large-N QCD have been further studied in [5][6][7]. The recent discovery of two pentaquark states of opposite parity [8] has reinforced the case for a new spectroscopic series of hadrons, in which diquarks (antidiquarks) replace antiquarks (quarks) in the classical scheme [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…During the refereeing we have been informed that the complete tables of isoscalar coefficients were presented in [47]. The tables presented here are analogous and differs only method of calculation.…”
mentioning
confidence: 99%